Disparities in outcomes of COVID-19 hospitalizations in native American individuals - Bime, Christian; Wang, Ying; Carr, Gordon; Swearingen, Dennis; Kou, Sherri; Thompson, Pam; Kusupati, Vinita; Parthasarathy, Sairam (Frontiers in Public Health, 2023)
Objectives: To investigate COVID-19-related disparities in clinical presentation and patient outcomes in hospitalized Native American individuals.Methods: Study was performed within 30 hospitals of the Banner Health system in the Southwest US and included 8,083 adult patients who were tested positive for SARS-CoV-2 infection and were hospitalized between March 1, 2020 and September 4, 2020.Bivariate and multivariate analyses were used to assess racial and ethnic differences in clinical presentation and patient outcomes.Results: COVID-19-related hospitalizations in Native American individuals were overrepresented compared to Non-Hispanic White individuals. Native American individuals had fewer symptoms at admission; greater prevalence of chronic lung disease in the elderly; 2 times greater risk for ICU admission despite being younger, and 20 times more rapid clinical deterioration warranting ICU admission. Compared to Non-Hispanic White individuals, Native American individuals had greater prevalence of sepsis, were more likely to require invasive mechanical ventilation, had a longer length of stay and higher in-hospital mortality, sepsis, invasive ventilation, and length of stay.Conclusions: Native American individuals manifested greater case-fatality rates following hospitalization than other race/ethnicities. Atypical symptom presentation of COVID-19, greater prevalence of chronic lung disease, and more rapid clinical deterioration may be responsible for observed higher hospital mortality underscoring the role of pulmonologists in addressing such disparities.